2007
DOI: 10.1119/1.2710480
|View full text |Cite
|
Sign up to set email alerts
|

When action is not least

Abstract: We examine the nature of the stationary character of the Hamilton action S for a space-time trajectory ͑worldline͒ x͑t͒ of a single particle moving in one dimension with a general time-dependent potential energy function U͑x , t͒. We show that the action is a local minimum for sufficiently short worldlines for all potentials and for worldlines of any length in some potentials. For long enough worldlines in most time-independent potentials U͑x͒, the action is a saddle point, that is, a minimum with respect to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
64
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 64 publications
(42 reference statements)
0
64
0
6
Order By: Relevance
“…In 2007, C. Gray and E. Taylor 8 presented a discussion about non-maximality of stationary action and showed that the solution of the equation of the simple harmonic oscillator is a saddle point of the action by assuming that the time in the Lagrangian integral is greater than the semi-period of the oscillator, which is physically relevant to allow oscillations in this range. This is also contained in Chapter 6 of the book of David Morin.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2007, C. Gray and E. Taylor 8 presented a discussion about non-maximality of stationary action and showed that the solution of the equation of the simple harmonic oscillator is a saddle point of the action by assuming that the time in the Lagrangian integral is greater than the semi-period of the oscillator, which is physically relevant to allow oscillations in this range. This is also contained in Chapter 6 of the book of David Morin.…”
Section: Introductionmentioning
confidence: 99%
“…8, which cite Refs. 9, 11, and 12) of a result which states that the action can never be maximum if the potential of the Lagrangian is velocity-independent, leaving for this potential, only the case of minimum or saddle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This latter viewpoint appears particularly useful in some applications in modern physics, including gravitational systems where relativistic effects are non-negligible, and systems in the quantum domain (cf. [6,7,8,13]). Our interests are more pedestrian; the stationary-action formulation has recently been found to be quite useful for generation of fundamental solutions to two-point boundary-value problems (TPBVPs) for conservative dynamical systems.…”
Section: Introductionmentioning
confidence: 99%
“…To explain the dynamics behind it would lead too far away from the presentation's focus, but reading QED and [9] is strongly recommended to deepen understanding of the far reaching influence of the PSA. For a deeper understanding of the quantummechanical basis of action, reading [10] is recommended.…”
mentioning
confidence: 99%